Pesticide poisoning of wildfowl in England and Wales - Fletcher, M R (Wildfowl, 2025)
The use of pesticides carries a potential risk for wild and domestic animals. The Wildlife Incident Investigation Scheme examines cases where animals are suspected of being poisoned by pesticides in England and Wales. During the years 1982-1991, 85 incidents involving wildfowl deaths were reported through the Scheme. The cause of death was identified in 53% of these, with agricultural chemicals implicated in 33%.